Transcriptional and Mutational Analysis of the Uptake Hydrogenase of the Filamentous Cyanobacterium Anabaena variabilis ATCC 29413 - Happe, Thomas (American Society for Microbiology, 2000)
A 10-kb DNA region of the cyanobacterium Anabaena variabilis ATCC 29413 containing the structural genes of the uptake hydrogenase (hupSL) was cloned and sequenced. In contrast to the hupL gene of Anabaena sp. strain PCC 7120, which is interrupted by a 10.5-kb DNA fragment in vegetative cells, there is no programmed rearrangement within the hupL gene during the heterocyst differentiation of A. variabilis. The hupSL genes were transcribed as a 2.7-kb operon and were induced only under nitrogen-fixing conditions, as shown by Northern blot experiments and reverse transcriptase PCR. Primer extension experiments with a fluorescence-labeled oligonucleotide primer confirmed these results and identified the 5′ start of the mRNA transcript 103 bp upstream of the ATG initiation codon. A consensus sequence in the promoter that is recognized by the fumarate nitrate reductase regulator (Fnr) could be detected. The hupSL operon in A. variabilis was interrupted by an interposon deletion (mutant strain AVM13). Under N(2)-fixing conditions, the mutant strain exhibited significantly increased rates in H(2) accumulation and produced three times more hydrogen than the wild type. These results indicate that the uptake hydrogenase is catalytically active in the wild type and that the enzyme reoxidizes the H(2) developed by the nitrogenase. The Nif phenotype of the mutant strain showed a slight decrease of acetylene reduction compared to that of the wild type.